Aspects of Salience in Phatic Tokens - Paronian, Shoushan (Armenian Folia Anglistika, 2005)
The article examines the role of consciousness in speech activity. Language application in different speech situations calls for various mental actions ranging from subliminal to conscious ones. Thus, in certain stereotypical speech situations the speakers automatically use conversational formulae readily available in the language. Without any conscious efforts they simply choose a combination of language signs appropriate to that particular situation. However, there are also speech situations which require a creative approach and mental efforts to pick the necessary language means. The analysis of phatic speech units makes it possible to suggest that in case of the application of the latter, it is necessary to use the ready-made conversation formulae and subconscious mental activity of selecting the language means.